Mental Health Struggles and Perceptions of Implementing Counseling Clinics on University Campuses: The Voices of Students - Oyeniyi, Odunola Funmilayo (International Journal of Applied Guidance and Counseling, 2022)
The number of students with severe mental health problems is a growing concern in Nigerian higher institutions with little or no counselors to attend to their needs. This study described university students’ experiences with mental health in academic settings through an interview. The findings revealed that university students deal with depression, anxiety, suicide, academic challenges, and addiction through qualitative interviews. To overcome these challenges, students must have mental health resources mainly received from the university to support these students. Therefore, as shown in this study, having a better understanding of these students’ mental health challenges, university faculty and staff can recognize students’ needs and effectively offer supportive campus counseling services. The university needs to be prepared to meet students academically, culturally, mentally, and emotionally. Implications of findings for educators, university administrators, and parents were discussed.